RESPON TANAMAN KACANG PANJANG (Vigna sinensis L.) TERHADAP PEMBERIAN PUPUK NPK PELANGI DAN PUPUK ORGANIK CAIR NASA - Bastianus Zaevi, Marisi Napitupulu, dan Puji Astuti (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
The objective of research was to study the response of long bean and its interaction upon the application of NPK Pelangi fertilizer and Nasa liquid organic fertilizer, as well as to find proper dosage for gaining better production of long bean.  The research was carried out from March to May 2013, at Melapeh Baru Village of Linggang Bigung Sub-District, West Kutai Regency.  The Randomised Block Design was employed for the research with factorial 4 x 4 and 3 replications.  The first factor was dosage of NPK Pelangi fertilizer (P) consisted of 4 sub-factors: no NPK Pelangi fertilizer application (p0), 1 kg/plot (p1), 3 kg/plot (p2), and 5 kg/plot (p3).  And the second factor was concentration of Nasa liquid organic fertilizer (N): no Nasa liquid organic fertilizer application (n0), 2 cc/liter-1 water (n1), 4 cc/liter-1 water (n2), and 6 cc/liter-1 water (n3).  Results of the research revealed that: (1) the dosage of NPK Pelangi fertilizer (P) affected significantly on the crop length, age of 80% crop flowered, number of fruit per crop, fruit length per crop.  The highest production was attained by the 5 kg/plot (p3) treatment with 4,9250 kg , and the least one was attained by the no NPK Pelangi fertilizer application (p0) treatment with only 2,9167 kg; (2) the Nasa liquid organic fertilizer application affect significantly on crop length, age of 80% crop flowered, number of fruit per crop, fruit weight per crop, fruit length, and production per crop.   The highest production was attained by 6 cc/liter-1 water (n3) treatment with 4,4833 kg , and the least one was attained by the no Nasa liquid organic fertilizer application (p0) treatment with only 2,9167 ; and (3) the interaction between the two above factors also affected significantly on crop length, age of 80% crop flowered, fruit weight per crop, fruit length per crop, production per crop.  The highest production was attained by the 5 kg/plot and 6 cc/liter-1 water (p3n3) treatment with 5,6333 kg, and the least one was attained by no application of NPK Pelangi and Nasa liquid organic fertilizer (p0n0) treatment with only 2,4667 kg.